2008
DOI: 10.1016/j.watres.2007.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate removal by mineral-based sorbents used in filters for small-scale wastewater treatment

Abstract: The mineral-based sorbents Filtra P, Polonite ® , natural wollastonite and water-cooled blast furnace slag (WCBFS) were studied in terms of their PO 4 removal performance. Results from a long-term column experiment showed that both Filtra P and Polonite ® removed > 95 % of PO 4 from the applied synthetic solution, and that the used filter materials had accumulated several (1.9-19) g kg -1 P. Phosphorus was removed also by natural wollastonite and WCBFS, but these materials were less efficient. Batch experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(73 citation statements)
references
References 20 publications
4
69
0
Order By: Relevance
“…At the end of the experiment, no signs of break-through (e.g., when the concentration in the influent is equal to the concentration in the effluent) could be detected and Johansson concluded that the slag materials were not saturated (Table 3). Gustafsson et al [25] reported an average P-removal of 86%, while there were hardly any differences between columns fed with P-solution or columns fed with real-life wastewater in the experiment carried out by Nehrenheim et al [18]. The results reported by Renman et al [27] also varied.…”
Section: Laboratory Column Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…At the end of the experiment, no signs of break-through (e.g., when the concentration in the influent is equal to the concentration in the effluent) could be detected and Johansson concluded that the slag materials were not saturated (Table 3). Gustafsson et al [25] reported an average P-removal of 86%, while there were hardly any differences between columns fed with P-solution or columns fed with real-life wastewater in the experiment carried out by Nehrenheim et al [18]. The results reported by Renman et al [27] also varied.…”
Section: Laboratory Column Testsmentioning
confidence: 97%
“…The aim of the study was to investigate the long-time performance of P-removal by two different BFS materials. Following these experiments, Gustafsson et al [25] evaluated the performance of BFS and several other materials, e.g., Filtra P, Polonite® and natural wollastonite with regard to P-removal using a column system also fed with a laboratory made P solution, containing 5 mg P/L. Column experiments using real-life wastewater have also been carried out by others; see for instance [26,27].…”
Section: Column Testmentioning
confidence: 99%
“…Another attractive feature of this technique is that the nutrient-loaded filters can be used in agriculture as phosphate fertilizer and soil conditioner [10]. A large number of materials from natural minerals to synthetic ones have been used as adsorbents to adsorb phosphate from wastewater [11][12][13][14][15]. Recently, the application of low cost and easily available materials for phosphate removal has been widely investigated, such as fly ash [16][17][18], blast furnace slag [19][20][21], iron oxide tailing [22], red mud [23,24], Ca-based adsorbents, and iron-based compounds [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…While as the distance from the inlet increases, the accumulated amount of phosphorus slightly decreases. Renman (2008) [18] and Gustafsson et al (2008) [9] investigated phosphorus removal potential of various filter materials (blast furnace slag, opoka, Polonite, limestone, wollastonite, Filtra P) in vertical columns and also came to a conclusion that phosphorus is mostly removed in the top layer of the substrate. Whereas in real wastewater treatment systems distribution of phosphorus sorbed in filter material may vary.…”
Section: Table 3 Amounts Of Removed Po4-pmentioning
confidence: 99%
“…The alternative way of phosphorus removal is to use materials which compose of elements that could bind phosphorus. The scientists have investigated phosphorus removal by using various materials such as sand, crushed marble, vermiculite, calcite, limestone, alunite, shellsand, Filtralite P, Polonite, Nordkalk Filtra P, wollastonite, alum, blast furnace slag, electric arc furnace slag, ochre, iron filings [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These materials are divided into three groups: natural materials, industrial by-products and man-made sorbents [1,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%